Investigation and Analysis of Cognition of Upper Limb Lymphedema in Postoperative Breast Cancer Patients - Xuelin YUAN; Na XIE; Liuya JIANG; Li LI; Jie JIA (康复学报)
Objective:A self-designed questionnaire was used to investigate the knowledge of upper limb lymphedema in postoperative breast cancer patients, and to provide direction for targeted health education.Methods:A total of 100 patients with pathologically diagnosed as breast cancer were selected as study objects by convenient sampling method. The patients were investigated with a self-designed questionnaire, which included general basic information, disease and treatment information, and cognition of lymphedema.Results:The survey showed that the patients had a better understanding of breast cancer postoperative complications, and the average mastery rate was 67.0%, but the awareness rate of lymphedema and its clinical manifestations, treatment methods, risk factors and nursing measures were low, which was 44.0%, 47.0%, 37.0%, 42.0%, 49.0%respectively. Among them, the awareness rate of treatment methods of lymphedema was the lowest (37.0%); the awareness rate of lymphedema risk factors was 42.0%.Conclusion:According to the results of knowledge of lymphedema related to breast cancer patients in the questionnaire, medical staff should strengthen the health education of breast cancer patients on lymphedema and its clinical manifestations, treatment approaches, risk factors and nursing measures and other aspects in the future work.